O Cavalo na Idade Média Portuguesa - Afonso Soares de Sousa (Medievalista)
The present article is a contribution to the study of the horse in the Middle Ages, in a period that extends between the X-XIII centuries. Geographically, this analysis comprises a space in profound transformations that is Portugal, during the process that took it from county to kingdom. The horse is treated here from a social, political, economic and daily perspective, considering its creation, its market value and symbolic value. It also addresses the political instrumentalization of this animal by the Portuguese monarchs.